ACO-Optimized DSTATCOM for Reactive Power Compensation in PV-Integrated Weak Grids - Rajasree R; Lakshmi D; Stalin K; Karthick Manoj R; P Jeyarani (Journal of Applied Data Sciences, 2026)
The integration of photovoltaic generation into weak distribution grids introduces voltage instability, reactive power imbalance, harmonic distortion, and prolonged transient response due to low short-circuit capacity and high grid impedance. This study proposes an Ant Colony Optimization-based Distribution Static Synchronous Compensator for improving voltage regulation and power quality in a PV-integrated weak grid. The optimization algorithm is used to tune the proportional–integral controller parameters by minimizing a composite objective involving PCC voltage deviation, reactive power error, total harmonic distortion, feeder power loss, and settling time. The proposed system is modeled in MATLAB/Simulink and evaluated against two benchmark configurations: an uncompensated weak-grid system and a conventional PI-controlled DSTATCOM. The results show that the proposed controller reduces PCC voltage deviation from 0.060 pu to 0.012 pu and reactive power demand from 150 kVAR to 5 kVAR. Total harmonic distortion decreases from 6.5% to 1.6%, while the power factor improves from 0.78 lagging to 0.995. In addition, feeder real-power losses are reduced from 45 kW to 28 kW, and the settling time decreases from 1.8 s to 0.5 s. These findings demonstrate that ACO-based controller tuning provides consistent improvements in voltage regulation, reactive power compensation, harmonic mitigation, feeder efficiency, and dynamic recovery under weak-grid operating conditions.